2015
DOI: 10.1016/j.pscychresns.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glutamate in striatal subregions in obsessive-compulsive disorder with proton magnetic resonance spectroscopy

Abstract: Glutamatergic signaling abnormalities in cortico-striatal circuits are hypothesized to lead to the repetitive thoughts and behaviors of obsessive-compulsive disorder (OCD). To test this hypothesis, studies have used proton magnetic resonance spectroscopy (1H MRS) to measure glutamatergic compounds in the striatum of individuals with OCD. However, none has used methods that could measure glutamate minimally contaminated by glutamine and γ-aminobutyric acid (GABA) in striatal subregions. Therefore, in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…This apparent discrepancy could be related to species, methodological, genetics, or other differences. However, our null finding in SAPAP3 KO mice is consistent with a recent report in medication-free adults with OCD using optimized striatal glutamate detection methods (61). As noted above, striatal glutamate abnormalities may become apparent in older SAPAP3 KO mice, especially after the onset of severe compulsive grooming.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This apparent discrepancy could be related to species, methodological, genetics, or other differences. However, our null finding in SAPAP3 KO mice is consistent with a recent report in medication-free adults with OCD using optimized striatal glutamate detection methods (61). As noted above, striatal glutamate abnormalities may become apparent in older SAPAP3 KO mice, especially after the onset of severe compulsive grooming.…”
Section: Discussionsupporting
confidence: 93%
“…While a number of striatal MRS studies in people with OCRD have been published (see 34 for review; and 61, 8892), none reported on lactate or GSH levels. This is due in part to the fact that MRS scan sequences used previously in humans were not optimal for quantifying these metabolites in striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, patients differ from one another both in the specific content of their OCD symptoms and in many other clinical features, including symptom severity, age of onset, course of illness, degree of insight, comorbidity, family history, and degree of functional impairment [61][62][63][64]. Some have reported that this variation in clinical presentation is reflected in different brain abnormalities [10,27,62,[65][66][67][68]. However, other differences in disease expression may be better explained by specific environmental and cultural factors.…”
Section: Why Take a Global Approach?mentioning
confidence: 99%
“…The authors interpret this finding as a demonstration of the interaction between serotonin and glutamate pathways in OCD pathology. Conversely, Simpson et al [37] reported no significant differences in glutamate levels in any of the 3 striatal regions (dorsal caudate, dorsal putamen, and ventral striatum) between OCD patients and matched healthy control subjects. It is noteworthy that the authors found negative results using a 1H-MRS imaging technique with a relatively high spatial resolution at 3.0 T, while MRS at 1.5 T in another study revealed significant elevations in glutamatergic compounds.…”
Section: Introductionmentioning
confidence: 95%
“…It is noteworthy that the authors found negative results using a 1H-MRS imaging technique with a relatively high spatial resolution at 3.0 T, while MRS at 1.5 T in another study revealed significant elevations in glutamatergic compounds. Therefore, at least some of these contradicting findings might be caused by differences in methodology [37].…”
Section: Introductionmentioning
confidence: 98%